The competence model of sports psychology consultants in China - Zhang, L. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: Nowadays, more and more nations focus on sports psychology consulting as a means of increasing athletic performance in both training and competition. Several previous studies shown that an excellent sports psychology consultant depends much more on depth of characteristics than on the knowledge or skills he possesses. This is termed competence in psychology and the administration area. This study aimed to determine competence in sports psychology consultants in China. This study also focused on competence theories in administration and psychology fields. Methods With the approach of Behavior Events Interview (BEI), this research interviewed 19 psychologists who serve as consultants for athletes in sports team, and intended to study the competence of sports psychology consultants in China. This research primarily constituted The Competence Dictionary on Sports Psychology Consultants of China. Based on the Competence Dictionary, this research constituted "The Competence Model of Sports Psychology Consultants in China" and explained each items of the model. Results / Discussion The frequency of competences is different between the excellent sports psychology consultants and the generic ones, indicating that the excellent coaches usually show their competence over the generic ones. This research finds the excellent consultants are different from the generic coaches in 8 types of competencies though the analysis of average scores with two items showing evident difference, which is similar to the result of psychologists` assessments. The competence model of sports psychology consultants in China consists of 8 competencies: Knowledge application, Detail observation, Potential interventions, Teamwork, Role-adjustment, Self-management, Peer communication and considering the long-range interest of athletes. The competence model of sports psychology consultants in China is significantly different from that of sports psychology consultants in foreign countries: the models share little in common. The differences were caused mainly by the different purpose of building the model, the special sports mechanics of China and the social and cultural barriers between east and west.